DETERMINAN FAKTOR FINANSIAL DAN NON FINANSIAL DALAM PENERAPAN KONSERVATISME AKUNTANSI PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN - Dewy Sekar Melati; Rida Prihatni; Etty Gurendrawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2023)
The financial report represents of company's financial status, and its preparation necessitates the application of accounting conservatism principles. However, the utilization of this principles remains limited in Indonesia. There is assumption that it is because financial factors (financial stress, capital intensity, and profitability) and non-financial factors (institutional ownership and managerial ownership). This research aims to examine the influence of financial factors and non-financial factors on accounting conservatism within the food and beverage sub-sector companies. The research employs a quantitative approach, population of companies within the food and beverage sub-sector, with a sample of 26 companies selected using purposive sampling technique. Based on the research findings, the regression analysis equation for panel data is derived as: KA = 0.055968 + 0.004050 FS + 0.047040 CI – 0.534471 PR – 0.096629 IO + 5.452554 + e. The Fixed Effect Model (FEM) is chosen. During the testing of classical assumptions, it is found that the regression model has a normal distribution, no multicollinearity, displays homogeneity, and no signs of autocorrelation. Result from this study concluded that financial stress, capital intensity, institutional ownership, and managerial ownership do not significantly affect accounting conservatism. But, profitability has a significant negative impact on accounting conservatism.